Injury profile among elite youth male football players in a German academy - Jaber, A.; Weishorn, J.; Berrsche, G.; Ott, H.; Bangert, Y. (International Journal of Sports Medicine, 2022)
Studies that report injuries in elite youth football players are scarce. So far, no such studies have been reported in Germany. The aim of this study is to descriptively and statistically report the incidence of injuries that resulted in time-loss = 4 days in the TSG Hoffenheim football academy by 138 male players aged between 12 and 19 years during one season. A total of 109 injuries were sustained by 76 players: 6.9 injuries occurred per 1000 hours of matches (95% CI, 5.0-9.6) and 0.7 injuries per 1000 hours of training (95% CI, 0.5-0.9) with a ratio of 9.8. Some 66% of all injuries occurred during matches. Injuries involved the lower limb (81%), upper limb (9%), head & neck (5%) and trunk injuries (5%). 21 (19%) of all injuries were regarded as severe and resulted in time-loss > 28 days. U16-U19 teams sustained more injuries (74, 68%) than U12-U15 (35, 32%) (P= 0.032). The most frequent diagnosis was thigh strain (22%). Time-loss ranged from 4-339 days (SD: 40, Average: 23). Many injuries were a result of strain. Available injury prevention programs should be adhered to more strictly. Dedicated epidemiological studies are needed to optimize focused injury prevention programs.